2015
DOI: 10.1177/0954407015572234
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of an internal combustion engine intake process using a low Mach number preconditioned density-based method with experimental comparison

Abstract: When air flows unsteadily in an internal combustion engine through its inlet pipe, chambers and valves, some effects such as friction and inertial forces have direct influence on the volumetric efficiency of the system. The work in this paper aims to investigate numerically and experimentally the pulsating phenomena present in an intake pipe of an internal combustion engine and to discuss the intake jet flow predictions through the novel implementation of a low Mach number preconditioned density-based method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It was also concluded that the tumble ratio of the cylinder could be increased by reducing the throat and inlet area. Falca˜o et al 18 studied the effect of friction and inertial forces on the volumetric efficiency of a system when air flows abnormally in an internal combustion engine through inlet pipe, chambers, and valves.…”
Section: Introductionmentioning
confidence: 99%
“…It was also concluded that the tumble ratio of the cylinder could be increased by reducing the throat and inlet area. Falca˜o et al 18 studied the effect of friction and inertial forces on the volumetric efficiency of a system when air flows abnormally in an internal combustion engine through inlet pipe, chambers, and valves.…”
Section: Introductionmentioning
confidence: 99%